Dwudziestolecie literackie - Zawada, Andrzej (Wroclaw : Wydawn. Dolnoslaskie, 1995)
An overview of 20th century Polish literature, intended for high school students.
Includes index.
Keywords: Polish literature -- 20th century -- History and criticism; Poland -- Intellectual life -- 1918-1945.